MOBILIZATION OF WORLD FLOWERING PLANTS SUPPLIES BASED ON DEVELOPMENT OF SYSTEMATIZED GENETIC COLLECTION OF ADAPTIVE AND AGRONOMIC VALUABLE TRAITS - A. A. Zhuchenko (Овощи России, 2012)
The problems of study and utilization of plant germplasm collections and arrangement of genetic resources based on botanical, functional, morphological, biochemical, and genetical principles are underlined in the article. The types of identified and systemized germplasm collections and genetic resources of flowering plants are described. The search path and methods of identification, differentiation, arrangement, and selection of genetic donors and germplasm collections of traits of ontogenetic and phylogenetic adaptation are shown in the article.